2013
DOI: 10.3896/ibra.1.52.5.05
|View full text |Cite
|
Sign up to set email alerts
|

Three species of native Thai honey bees exploit overlapping pollen resources: identification of bee flora from pollen loads and midguts fromApis cerana, A. dorsataandA. florea

Abstract: In this study, we investigated the bee flora utilised by the Thai honey bees, Apis cerana, A. dorsata and A. florea in Nan province, northern Thailand, through the identification of pollen grains from their pollen loads and midguts. We compared the pollen grains morphologically to match with local flowering plants and determined their protein concentration using a Bradford assay. The results showed that 8 families and 15 species were found by pollen load analysis whilst 12 families and 25 species were found fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…For size reference, the average ITD of A. mellifera can range between 2.93 and 3.07 mm (Kolmes & Sam, 1991; Santos & Serrão, 2006). All three Apis species are polylectic and forage on diverse plant species (Suwannapong et al ., 2013; Stewart et al ., 2018). While it is possible that some of the bee‐visited plant species are not actually pollinated by bees, we were still interested in the precision of pollen placement on bee visitors, since bilateral symmetry, corolla fusion and horizontal orientation are expected to constrain the movement of all floral visitors to some extent, not just actual pollinators, and flowers with fewer stamens are expected to have fewer opportunities to contact multiple areas of a floral visitor’s body.…”
Section: Methodsmentioning
confidence: 99%
“…For size reference, the average ITD of A. mellifera can range between 2.93 and 3.07 mm (Kolmes & Sam, 1991; Santos & Serrão, 2006). All three Apis species are polylectic and forage on diverse plant species (Suwannapong et al ., 2013; Stewart et al ., 2018). While it is possible that some of the bee‐visited plant species are not actually pollinated by bees, we were still interested in the precision of pollen placement on bee visitors, since bilateral symmetry, corolla fusion and horizontal orientation are expected to constrain the movement of all floral visitors to some extent, not just actual pollinators, and flowers with fewer stamens are expected to have fewer opportunities to contact multiple areas of a floral visitor’s body.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the size category, pollen was found ranging in size from very small to very large. Suwannapong et al (2013) identified pollen from the A. cerana midgut recorded as many as 25 species in Northern Thailand. They found that the favored pollen source plant of A. cerana was Mimosa pudica.…”
Section: Resultsmentioning
confidence: 99%
“…[ 78 ] in northern Thailand. Moreover, this parasite has been detected in A. cerana , A. florea, and the non-native A. mellifera in central Thailand [ 79 ]. Our results also showed that N. ceranae was detected in A. cerana samples from Chiang Mai, Chumphon, and Samui Island, but not in those collected from the northeast region.…”
Section: Discussionmentioning
confidence: 99%